2016
DOI: 10.1002/cam4.850
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cancer and Alzheimer's disease in a U.S. Medicare population

Abstract: Several studies have reported bidirectional inverse associations between cancer and Alzheimer's disease (AD). This study evaluates these relationships in a Medicare population. Using Surveillance, Epidemiology, and End Results (SEER) linked to Medicare data, 1992–2005, we evaluated cancer risks following AD in a case–control study of 836,947 cancer cases and 142,869 controls as well as AD risk after cancer in 742,809 cancer patients and a non‐cancer group of 420,518. We applied unconditional logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 40 publications
5
71
3
Order By: Relevance
“…[2, 4, 13, 14] However, our results showed that incident and prevalent cancers should not be combined into a single “any cancer” group because they have different associations AD and dementia. We are only aware of two prior studies that limited analyses to prevalent cancers.…”
Section: Discussionmentioning
confidence: 97%
“…[2, 4, 13, 14] However, our results showed that incident and prevalent cancers should not be combined into a single “any cancer” group because they have different associations AD and dementia. We are only aware of two prior studies that limited analyses to prevalent cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, multiple studies suggest an inverse association between cancer and dementia, in particular for Alzheimer disease (AD) . In 1990, Yamada et al investigated risk factors for dementia in atomic‐bomb survivors and observed that the odds of having cancer prior to AD was 70% lower in patients with AD compared to persons without AD.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
“…Few studies investigated the relation of cancer with other diseases including stroke, automobile injuries, osteoarthritis and macular degeneration, which were used as negative control diseases . In case of survival bias, cancer patients would also have a decreased risk of these diseases.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
See 2 more Smart Citations